Urban structure, commuting burden, and employment status of labour forces in an Australian city. (May 2021) - Li, Tiebei; Dodson, Jago; Goldie, Xavier
Abstract: Understanding the productivity effects of worker commuting burdens is essential for appraisals of urban planning and investment strategies designed to improve urban productivity. However, the extant urban planning literature lacks systematic analysis of the influence of commuting costs on labour mobility, employment engagement, and productivity. This paper provides the first ever detailed analysis of mobility and commuting burdens for workers in a range of industries and occupational groups in Melbourne, Australia. Linking commuting burdens and measures of employment status in urban areas, this paper finds that the labour force in areas experiencing high commuting burdens exhibit lower levels of engagement with job markets. This research further reveals important variations in such relationships across diverse industry and occupation groups. The results provide urban policy makers with better information about urban transport and employment patterns, thus enabling them to investigate alternative approaches to investing in housing and transport infrastructure to reduce worker commuting burdens and improve economic performance.